Studi Pengaruh Co-doping Neodymium (Nd) Terhadap Sifat Fisik Elektrolit Ce0.9Gd1-xNdxO2-z dengan Metode Sol-Gel untuk Aplikasi IT-SOFC - Jarot Raharjo; masumi .; Wahyudin . (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Neodymium and Gadolinium co-doped ceria (Ce0.9Gd1-xNdxO2-z) is a promising alternative as a solidelectrolyte for intermediate temperature solid oxide fuel cell (IT-SOFC) due to its low operating temperatureand its high electrical conductivity. Ce0.9Gd1-xNdxO2-z powders, with x=0.25, 0.50 and 0.75mol% ofneodymium were successfully syhnthesized with a sol-gel method and citric acid as an organic precursor.The samples were calcined at temperature of 750oC for 5 hours. The powders properties were thencharacterized by X-ray diffraction, scanning electron microscopy, thermal gravimetry analysis, and thesintered pellets were evaluated by Archimedes method for calculate the density. Sintered Ce0.9Gd1-xNdxO2-zsamples exhibited the maximum theorical density of 97% which is suitable for solid electrolytes. TheCe0.9Gd1-xNdxO2-z powders consist of face-centered cubic fluorite ceria structure confirmed with x-raydiffraction (XRD). methodology investigated showed a better control of stoichiometry, impurities, and lowcost.